2000
DOI: 10.1063/1.1311597
|View full text |Cite
|
Sign up to set email alerts
|

High figure of merit in partially filled ytterbium skutterudite materials

Abstract: We present evidence of a relatively high dimensionless figure of merit (ZT) in a polycrystalline skutterudite partially filled with ytterbium ions. The small-diameter yet heavy-mass Yb atoms partially filling the voids of the host CoSb3 system exhibit low values of thermal conductivity while the quite favorable electronic properties are not substantially perturbed by the addition of Yb. This combination is ideal for thermoelectric applications exemplifying the “phonon-glass electron-crystal” concept of a therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
343
1
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 540 publications
(363 citation statements)
references
References 16 publications
17
343
1
2
Order By: Relevance
“…10 Among these elements, Yb is one of the most effective fillers to lower lattice thermal conductivity (κ L ) due to its heavy atomic mass and small ionic radius, which result in the lowest rattling frequency of~42 cm − 1 in CoSb 3 . 10,11 Despite being studied extensively because of its demonstrably good TE properties (ZT~1.2-1.4), [11][12][13][14][15][16][17] the filling fraction limit (FFL) of Yb has still not been conclusively determined. Various authors have reported substantially different transport properties for a wide range of Yb filling fractions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Among these elements, Yb is one of the most effective fillers to lower lattice thermal conductivity (κ L ) due to its heavy atomic mass and small ionic radius, which result in the lowest rattling frequency of~42 cm − 1 in CoSb 3 . 10,11 Despite being studied extensively because of its demonstrably good TE properties (ZT~1.2-1.4), [11][12][13][14][15][16][17] the filling fraction limit (FFL) of Yb has still not been conclusively determined. Various authors have reported substantially different transport properties for a wide range of Yb filling fractions.…”
Section: Introductionmentioning
confidence: 99%
“…Various authors have reported substantially different transport properties for a wide range of Yb filling fractions. [11][12][13][15][16][17][18] Shi et al 19 first determined the theoretical FFL of Yb in CoSb 3 to be 0.2 using ab initio calculations. This was done by considering the competing effects of secondary phases (mainly YbSb 2 ); later, Mei et al 20 calculated the Yb FFL of 0.3 using a similar density functional theory approach.…”
Section: Introductionmentioning
confidence: 99%
“…We argue that a significant decrease in the carrier concentration in bulk nanocomposites Ti 9 Ni 7 Sn 8 as observed from the Hall data, reduces the Fermi energy and consequently resulted in an increased Seebeck coefficient. 40 Though mechanism of increased aðTÞ and rðTÞ at room temperature has been presented here, however, understanding on the aðTÞ and rðTÞ variation with higher temperature requires high temperature Hall measurement which will be the future avenue of this research and needs to be investigated further. Thus, mechanisms for enhancing the electronic properties is primarily interface electron scattering, 23,27,[36][37][38] electron injection through metallic inclusions, 24,25 and direct dependence of Seebeck coefficient on reduced Fermi energy, n as suggested by Nolas et al 40 In conclusion, a generic composition Ti 9 Ni 7 Sn 8 with VEC ¼ 17.25, synthesized by arc melting followed by SPS resulted to an in-situ bulk nanocomposite consisting of HH, FH, and a traces of nano-sized Ti 6 Sn 5 phase.…”
mentioning
confidence: 90%
“…The figure was compiled by using various literature sources. [56][57][58][59][60] ChemSusChem 2010, 3, 44 -58 2010 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim www.chemsuschem.org trical conductivity typical of crystalline materials and, at the same time, a very low lattice thermal conductivity typical of an amorphous solid (so-called "electron-crystal, phonon-glass" materials). [62][63][64][65] The temperature dependence of ZT values of two n-type materials that belong to skutterudite (Yb 0.2 Co 4 Sb 12 ) and clathrate (Ba 8 Ga 16 Ge 30 ) families of inclusion compounds are presented in Figure 9.…”
Section: Thermoelectric Materialsmentioning
confidence: 99%